2013
DOI: 10.1021/jp406662n
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational State Dependence of Interfacial Electron Transfer: Hot Electron Injection from the S1 State of Azulene into TiO2 Nanoparticles

Abstract: Synthesis of 6-methyl-azulene-2-carboxylic acid.Anhydrous cyclohexane (Acros Organics) was freshly distilled off sodium/benzophenone prior to use. Toluene was purchased anhydrous (Acros Organics) and used as received. Acetonitrile, methanol and ethanol were purchased HPLC grade (Acros Organics) and used without further purification. The 6-methyl-azulene (tech.) was purchased from Maybridge Ltd. Bis(pinacolato)diboron (B 2 Pin 2 , 98%), chloro(1,5-cyclooctadiene)iridium(I) dimer, 2,2'bipyridine (2,2'-bpy, 99%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…Carrier−carrier and carrier−phonon interactions regulate the relaxation of high-energy "hot" carriers, 18,19 while the energy level alignment and lifetime of the excited state controls charge injection from sensitizers to the semiconductor. 20 Temperature modulates the semiconductor energy levels due to excitation of phonons, which affects electron−phonon coupling and thermal conductance at a metal−semiconductor interface. Recent, ab initio calculations on TiSi 2 (metal)−Si (semiconductor) interface revealed that the strength of the coupling between electrons and interfacial joint phonon modes is similar to the strength of electron−phonon coupling in bulk metals and that the thermal conductance can be comparable to the phonon−phonon conductance across the interface.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Carrier−carrier and carrier−phonon interactions regulate the relaxation of high-energy "hot" carriers, 18,19 while the energy level alignment and lifetime of the excited state controls charge injection from sensitizers to the semiconductor. 20 Temperature modulates the semiconductor energy levels due to excitation of phonons, which affects electron−phonon coupling and thermal conductance at a metal−semiconductor interface. Recent, ab initio calculations on TiSi 2 (metal)−Si (semiconductor) interface revealed that the strength of the coupling between electrons and interfacial joint phonon modes is similar to the strength of electron−phonon coupling in bulk metals and that the thermal conductance can be comparable to the phonon−phonon conductance across the interface.…”
mentioning
confidence: 99%
“…Efficient systems are commonly characterized by an ultrafast injection (<1 ps) followed by a slow exponential decay(s) due to charge recombination. Carrier–carrier and carrier–phonon interactions regulate the relaxation of high-energy “hot” carriers, , while the energy level alignment and lifetime of the excited state controls charge injection from sensitizers to the semiconductor …”
mentioning
confidence: 99%
“…The observation that Az S 2 can participate in eT led us to bind Az 2 @OA 2 and GAz@OA 2 capsuleplexes to TiO 2 colloidal aqueous suspensions and films cast on glass to study TiO 2 as the electron acceptor. Indeed, it has been demonstrated that the S 2 excited state of azulene derivatives lies above the conduction band of this metal oxide, as photoinduced electron transfer from the S 2 state of azulene to the conduction band of TiO 2 takes place efficiently, following selective excitation of the azulene chromophore. , As carboxylic acids are known to bind covalently to metal oxide semiconductors, some of the COOH groups present on OA’s exterior can be expected to bind to the TiO 2 nanoparticle surface, whether these are diluted colloidal solutions or mesoporous films. …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it has been demonstrated that the S 2 excited state of azulene derivatives lies above the conduction band of this metal oxide, as photoinduced electron transfer from the S 2 state of azulene to the conduction band of TiO 2 takes place efficiently, following selective excitation of the azulene chromophore. 20,64 As carboxylic acids are known to bind covalently to metal oxide semiconductors, some of the COOH groups present on OA's exterior can be expected to bind to the TiO 2 nanoparticle surface, whether these are diluted colloidal solutions or mesoporous films. 65−67 An important prerequisite is that the Az 2 @OA 2 and GAz@ OA 2 capsuleplexes are stable in the experimental conditions used for binding.…”
Section: ■ Resultsmentioning
confidence: 99%
“…3739 Therefore, we conclude that the S 1 excited state is located below the conduction band edge at the TiO 2 interface and the slow decay is likely governed by injection into defect trap states. 40 Several TA measurements on similar systems found fast HET by evaluating the rise time of the probe signal around 600 nm. 38, 39 This assumption appears to be unreasonable in our case because the rise time resembles our instrument response function of 28 fs (Figure 7b).…”
Section: Resultsmentioning
confidence: 99%